Bridging the Gender Gap in Post-Cardiac surgery Outcomes: The Need for Targeted Strategies - alebrahim, khaled (Jordan Medical Journal, 2025)
We read with great interest the article by Abu Hantash et al., (The Acute vs Chronic Post-CABG Complications: Does Gender Matter? A Retrospective Cohort Study from the Jordan University Hospital Records)[1]. The authors should be commended for addressing this important topic, as gender-specific outcomes in cardiac surgery remain a matter of debate and ongoing research. Our own work in this field has shown consistent findings that support the notion of gender differences in postoperative outcomes after CABG . In our study, “Effect of Gender on Postoperative Outcome and Duration of Ventilation After Coronary Artery Bypass Grafting ” [2], we demonstrated that female patients had longer durations of postoperative ventilation and were at increased risk for certain complications compared with males. Furthermore, in another retrospective study from Saudi Arabia, “Female Gender in Cardiac Surgery: Is it Still a Significant Risk?” (3), we highlighted that female gender continues to be associated with higher morbidity despite advances in surgical techniques and perioperative care. These disparities may be attributed to multiple interconnected factors, including biological differences in pain perception and healing, psychiatric vulnerability with higher rates of anxiety and depression, and heightened emotional liability[3,4]. Women frequently report worse postoperative quality of life and greater symptom burden compared to men[5] . Furthermore, women often enter surgery with higher expectations of functional recovery, which, when unmet, may exacerbate dissatisfaction and perceived impairment[2-4]. Taken together with the findings of Abu Hantash et al., these studies emphasize that gender remains an independent risk factor for outcomes following CABG. This highlights the necessity of preoperative risk stratification and tailored perioperative strategies to mitigate these differences and improve outcomes, particularly for female patients[4]. We congratulate the authors on their valuable contribution and hope that further multicenter studies will help refine our understanding of gender-related outcomes in cardiac surgery.